Adjuvant therapy for pT1a-m3/pT1b esophageal squamous cell carcinoma after endoscopic resection: Esophagectomy or chemoradiotherapy? A critical review. (March 2020) - Tsou, Yung-Kuan; Lee, Cheng-Han; Le, Puo-Hsien; Chen, Bo-Huan
Highlights: ER followed by adjuvant therapy can be a new treatment option. Adjuvant esophagectomy is better than adjuvant CRT in terms of tumor recurrence. Tumor with invasion to ≥ sm2 plus lymphovascular invasion is a high-risk of relapse. Patients with a high-risk should be treated with adjuvant esophagectomy. Patients with a nonhigh risk can be treated with adjuvant chemoradiotherapy. Abstract: Endoscopic resection (ER) combined with adjuvant therapy appears to be a new treatment for esophageal squamous cell cancers (ESCC) invading to deep mucosa (pT1a-m3) or submucosa (pT1b). Adjuvant therapy can take the form of esophagectomy or chemoradiotherapy (CRT), but it is unclear which treatment is better. This review is to explore the outcomes of adjuvant therapy between esophagectomy and CRT for the treatment of pT1a-m3/pT1b ESCC after ER. Ten relevant studies with a total of 285 patients were included. The reported 5-year overall survival rates ranged between 90–100 % for ER-esophagectomy and 75–85 % for ER-CRT. ESCC with the invasion of ≥ sm2 combined with lymphovascular involvement was associated with a high-risk of relapse in patients receiving ER-CRT, but not in ER-esophagectomy. In conclusion, patients with a high-risk of relapse should be treated with ER-esophagectomy; ER-CRT may be used as an alternative treatment for patients with a nonhigh risk of relapse.